The one-year incidence of stroke in patients with atrial fibrillation in Jordan and its associated factors - Al-Shatanawi, Tariq N.; Alkouri, Osama; Khader, Yousef; ALSalamat, Husam; Qaladi, Omar Aawadh; Jarrah, Mohamad; Ababneh, Anas; Al-Awaisheh, Raed; Zamil, Taqialdeen; Hammoudeh, Ayman (Frontiers in Medicine, 2024)
Background: An elevated risk of stroke is linked to atrial fibrillation (AF). Effective care and prevention measures for individuals with AF require an understanding of the factors impacting the incidence of stroke in this population. Evidence regarding the incidence of stroke among patients with AF is insufficient in Jordan. This study aimed to determine the incidence of stroke and its associated factors among patients with AF in Jordan. Methods: The Jordan Atrial Fibrillation Registry JoFib was used to identify a total of 2020 AF patients meeting the study inclusion and exclusion criteria. Demographics, clinical characteristics, and the CHA2DS2-VASc score-based evaluation of stroke risk were extracted from the registry. Results: This study encompassed 2020 participants diagnosed with AF, with 925 (45.8%) being men and 1095 (54.2%) women. The one-year stroke incidence among the 2020 AF patients was 3.4%. Notably, stroke incidence significantly increased with age (p = 0.04) and was associated with the history of stroke (7.4% vs. 2.7%), hypertension (3.9% vs. 1.9%), and diabetes (5.1% vs. 2.1%). In the multivariate analysis, diabetes (OR = 2.6, 95% CI: 1.5 - 4.4, p = 0.001) and history of stroke (OR = 2.6, 95% CI: 1.5 - 4.6, p = 0.001) were significantly associated with stroke incidence. Conclusion: This study emphasizes Jordan's high stroke rate among AF patients. Diabetes and prior stroke history are associated with increased odds of stroke, like all stroke patients. These results highlight the necessity for specialized management strategies among AF patients and highlight the significance of thorough risk assessment and focused interventions to reduce stroke risk in AF patients.